(untitled) (Global Journal of Management and Business Research, 2014)
The area of information technology (it) has undergone constant changes that, consequently, impact directly on professional and in companies that work with this sector. The aim of this study was to identify the profile and motivational inclination in the career of it professional. This is a field where applied questionnaires closed in professionals. The sample was composed of 27 professionals in companies participating in the CIO of Rio Grande do Sul. The two instruments used were the inventory of Schwartz values (IVS) that offer some perspectives of appreciation of employee matching your goals and interests, and the other instrument was the questionnaire by Edgar Schein on professional inclination, which allows you to identify the relationship and prospects of those with work and their lives. With the results exposed it was found, that it professionals surveyed here are self-determined, individuals value the lifestyle, are benevolent and hedonists, seek well-being and job satisfaction and love challenges. I concluded then that professionals and students are or will be mostly professionals in search of constant challenges and personal and professional satisfaction, adapting the work in the best possible way to your lifestyle.